Impact of Employee Adoption as a Moderator between E-Governance and Work Life Balance in Public Sector Organizations of Punjab - Muhammad Rizwan Anjum; Wahab Ahmed; Hira Azhar (Review Journal of Social Psychology & Social Works, 2025)
Past two decades have witnessed a paradigm shift in the way governments work in serving the public. Electronic Governance (E-governance) took over the humans in much quantum/ somewhere even completely. Pakistan is amongst countries incorporating ICT and digitization. ICT are believed to reduce work load and improve employee’s work conditions however it’s adoption remains a crucial aspect. This study was conducted on public sector organizations to know the relationship between e-government practices and work life balance (hereinafter WLB) with moderating effect of employee adoption. The data was collected from ten public service delivery organizations. Results show a significant relationship between e-government practices and WLB.